Ten years follow up of a chronic tubercular osteomyelitis of the proximal tibia in infancy - Sinha, Akansha; Iyengar, Raju; Patnala, Chandrasekhar (International Journal of Research in Orthopaedics, 2020)
Primary tuberculous osteomyelitis accounts for less than 10% of extra pulmonary tuberculosis in childhood.In about 50% of the patients, the vertebrae are the sites of skeletal involvement. Solitary bone TB is rare in infancy and has non specific findings and can be misdiagnosed easily. A 12 month old infant, presented with fever, pain, swelling in left knee, difficulty in moving left lower limb and inability to bear weight for 15 days at Nizam’s institute of medical sciences, Hyderabad, in 2010. She was managed conservatively with injectable antibiotics, initially. After 15 days fever and swelling recurred. A biopsy was performed which showed plenty of polymorphs. A month later with second recurrence she was operated by means of debridement and curettage. Subsequent biopsy and culture revealed active Mycobacterial tuberculous infection. Anti-tubercular treatment titrated to her body weight was administered for 12 months and patient was followed up. The patient’s general condition improved with betterment in laboratory parameters, resolution of the lesion, without any sequelae. Upon a close follow up of 10 years (2010-2020), no residual deformity was noted and excellent clinical outcome achieved. Skeletal TB without spinal involvement in children is rare and it does not have any pathognomonic radiographic or clinical characteristics. Physis can heal gradually and full range of motion of the adjacent joints can be maintained. Tuberculosis should be an essential differential diagnosis while addressing cases with similar presentation in endemic regions like India. As clinical and radiological findings may be indistinguishable from malignant disease, tuberculous osteitis should be excluded in infants presenting with undiagnosed bone lesions despite been vaccinated with Bacille Calmette Guerin at birth.